Endometriosis and cumulative live birth rate after fresh and frozen IVF cycles with single embryo transfer in young women: no impact beyond reduced ovarian sensitivity—a case control study - Feichtinger, Michael (J Assist Reprod Genet, 2019)
PURPOSE: To investigate the impact of symptomatic and surgically confirmed endometriosis on ovarian sensitivity index (OSI) and cumulative live-birth rates (LBR) using predominantly single embryo transfer (SET). METHODS: Cross-sectional case-control study in a University-based ART program. Women with symptomatic and surgically confirmed endometriosis (N = 172), who underwent IVF/ICSI at Karolinska University Hospital were compared to controls without clinically suspected endometriosis (N = 2585). Two thousand seven hundred fifty-seven patients underwent 8236 treatment cycles (4598 fresh and 3638 frozen cycles). Primary outcome measures included Ovarian Sensitivity Index (OSI) estimated as collected oocytes/FSH dose and cumulative LBR/oocyte pickup (OPU). Generalized estimated equation (GEE) model accounting for dependencies between consecutive treatments were applied. Secondary outcomes included number of oocytes, pregnancy rate per OPU and per ET, LBR per ET, and miscarriage rate. RESULTS: Patients diagnosed with endometriosis had significantly fewer oocytes collected (8.47 vs. 9.54, p = 0.015) and lower OSI (p = 0.011) than controls. There were no differences in cycle cancelations (p = 0.59) or miscarriages (p = 0.95) between the two groups. Cumulative LBR/OPU did not differ between women with endometriosis and controls (35.6% vs. 34.7%, respectively, p = 0.83). In both groups, more than 60% of women had consecutive FETs after fresh ETs (p = 0.49) with SET in > 70% of cases. The results were similar whether ovarian endometrioma was present or not. CONCLUSIONS: Our data support that a diagnosis of endometriosis, with or without present endometrioma, does not negatively affect ART cumulative results. The impact of endometriosis was discernible on OSI but not on clinical relevant outcomes including pregnancy and LBR.